2004
DOI: 10.1139/z04-066
|View full text |Cite
|
Sign up to set email alerts
|

The effects of crayfish predation on phenotypic and life-history variation in fathead minnows

Abstract: Ecological theory predicts that the timing of the transition between life-history stages should vary with the costs and benefits associated with each stage. For example, the timing of hatching or metamorphosis may vary with the predation risk in each stage. Predator-induced changes in hatching time are well documented in some taxa but have not been reported in fishes. We provide the first empirical evidence that a species of fish can alter its hatching time in response to predator cues. We showed that fathead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…similarly context-dependent hatching timing has been shown in other taxa (Sih and Moore, 1993;Chivers et al, 2001;Li, 2002;Wedekind, 2002;Kusch and Chivers, 2004;Moreira and Barata, 2005). Here we show that A. callidryas embryos also modulate the amount of information on which their hatching decision is based depending on the amount of time, or risk, entailed in gathering that information.…”
Section: Studying Egg Behaviorsupporting
confidence: 71%
“…similarly context-dependent hatching timing has been shown in other taxa (Sih and Moore, 1993;Chivers et al, 2001;Li, 2002;Wedekind, 2002;Kusch and Chivers, 2004;Moreira and Barata, 2005). Here we show that A. callidryas embryos also modulate the amount of information on which their hatching decision is based depending on the amount of time, or risk, entailed in gathering that information.…”
Section: Studying Egg Behaviorsupporting
confidence: 71%
“…Cues from both predators (Moore et al 1996;Smith and Fortune 2009;Miner et al 2010) and pathogens (Kiesecker et al 1999;Wedekind 2002) have been observed to alter hatching time. These cues can be quite specific, allowing animals to distinguish between predators and nonpredators, and even predator diets (Chivers et al 2001;Kusch and Chivers 2004). Induced responses can equally be elicited from injured or infected conspecifics (Kiesecker et al 1999;Chivers et al 2001;Wedekind 2002;Miner et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Treefrogs embryos that hatch early because of a snake enter the pond at a smaller size and are more susceptible to predators that prey upon free-living larvae (Warkentin 1995). To date, predators are known to alter, either accelerate or delay, time-to-hatching in 14 species of frog (reviewed by Warkentin 2007), a species of salamander (Moore et al 1996;Sih and Moore 1993), a species of Wsh (Kusch and Chivers 2004), a species of spider (Li 2002), and a species of fairy shrimp (De Roeck et al 2005). Evidence suggests that the presence of predators also aVects when a mosquito and some crustaceans hatch (Blaustein 1997;Livdahl et al 1984).…”
Section: Introductionmentioning
confidence: 99%